Fire and fury [compact disc, unabridged] : inside the Trump White House - Wolff, Michael, 1953- (Macmillan Audio, 2017)
The first nine months of Donald Trump's term were stormy, outrageous, and absolutely mesmerizing. Now, thanks to his deep access to the West Wing, bestselling author Michael Wolff tells the story of how Trump launched a tenure as volatile and fiery as the man himself. Wolff provides a wealth of new details about the chaos in the Oval Office.